Integrasi Model Pembelajaran Kooperatif berbasis Metode Teams Games Tournament pada Media Rukhsah Crossword Puzzle dalam Meningkatkan Partisipasi Belajar Siswa - Farandika Nanda Pratama; Alfi Nikmah; Fitra Irpandi (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited application of the cooperative learning model using the Teams Games Tournament (TGT) method in fiqh subjects, particularly on the topic of rukhsah, despite the persistent issue of low student participation in Islamic Religious Education (PAI) classes under the Kurikulum Merdeka. The aim of this research is to describe the implementation process, challenges, and student responses to the integration of the TGT cooperative learning model through the “Rukhsah Crossword Puzzle” media. A qualitative field research approach was employed, involving 27 seventh-grade students at SMP 1 Kudus. Data were collected through observation, interviews, and documentation, and analyzed using triangulation of sources, techniques, and timing. The findings indicate that the TGT-based cooperative model significantly enhances student participation; students were more engaged in discussions, showed enthusiasm, and demonstrated improved comprehension of the material. Challenges such as classroom noise and technical issues were managed effectively through proper classroom management and device preparedness. The study concludes that the TGT model combined with crossword puzzle media creates an interactive and enjoyable learning environment, contributing to the growing body of literature on PAI instruction. The implications suggest that this model can serve as a practical reference for teachers in designing participatory learning and opens opportunities for further research across different topics, methods, and educational levels.